SEMANTIC ANALYSIS OF OLIVIA RODRIGO'S SONG DRIVERS LICENSE USING CONTEXTUAL MEANING THEORY - Luthfiani, Qori; Heriyati, Nungki (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2023)
This study analyzes literary works in the form of song lyrics where the data is taken from one of Olivia Rodrigo's songs entitled 'Drive License' which was released on January 8 2021. The song is intended for a lover who betrayed her. This study aims to analyze the meaning of the song. In this song, the man is claimed to only give women false hope and a feeling of disappointment over the betrayal of their lover. This study uses an analysis that examines semantic meaning using the Contextual Meaning theory approach by Pateda (2010) to analyze the meaning of feelings in the song lyrics, namely the context of the speaker's mood, for example sad, disappointed, afraid, irritated. This study uses a qualitative descriptive method which is by making observations using phenomena or facts obtained by conventional data. The results of the analysis illustrate that the lyrics of the song 'Drive License' adopt a sketch aesthetic and describe Olivia Rodrigo's healing in her broken heart which shows her feelings of sadness and disappointment towards the man who hurt her. Keywords: Semantic, Contextual meaning, Olivia Rodrigo, Drivers License